Some practical aspects of using balanced scorecard tools - Yu. I. Rastova; М. A. Rastov (Омский научный вестник: Серия "Общество. История. Современность")
This publication demonstrates the possibility of using the indicator «correspondence of the category of pieceworkers to the category of work performed» as an indicator that provides identification, monitoring, forecasting of production losses, as well as setting goals for preventive, corrective and improvement actions. The methodological basis of the study is the concept of a balanced scorecard that integrates the factors and conditions for the effective achievement of business goals into process and numerical models. Cohort and variance analysis are used as methods for studying cause-and-effect relationships. It is concluded that the tools of the balanced scorecard allow the best way to transform data into meaningful, ready-to-use information for decision-making.